2020
DOI: 10.1002/smr.2265
|View full text |Cite
|
Sign up to set email alerts
|

Investigating diversity and impact of the popularity metrics for ranking software packages

Abstract: Context Community‐based collaborative approach in open source software paradigm promotes reuse of existing software packages. There are several repositories (e.g., npm) for packages and have their own set of metrics for ranking. Objective This study explores the diversity of different popularity metrics and also the relationship between popularity metrics and development activity of the packages. Another aim is to create a package popularity index by aggregating a set of noncollinear popularity metrics. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It allows performing the semantic analyses and grouping (clustering) of the set of words (or similar expressions) from the documents corpus. The data points in the same group (cluster) are more similar to each other, in comparison to the data points in other groups (Saini et al, 2020 ). In this case study, we have applied the LDA (Latent Dirichlet allocation) algorithm, to analyze the comments (feedbacks or suggestions) of the respondents (teachers and students) concerning the conduct of online teaching and learning during the COVID-19 pandemic outbreak.…”
Section: Analyzing the Outcomes Of Online Teaching And Learning With The Conduct Of Online Survey: A Case Studymentioning
confidence: 99%
“…It allows performing the semantic analyses and grouping (clustering) of the set of words (or similar expressions) from the documents corpus. The data points in the same group (cluster) are more similar to each other, in comparison to the data points in other groups (Saini et al, 2020 ). In this case study, we have applied the LDA (Latent Dirichlet allocation) algorithm, to analyze the comments (feedbacks or suggestions) of the respondents (teachers and students) concerning the conduct of online teaching and learning during the COVID-19 pandemic outbreak.…”
Section: Analyzing the Outcomes Of Online Teaching And Learning With The Conduct Of Online Survey: A Case Studymentioning
confidence: 99%
“…Regarding the OSS popularity, Sanjani et al [32] observed that factors other than engineering quality are at play in popularity of OSS. Saini et al [33] analysed a number of popularity metrics of OSS reusable packages, and found that most of them are correlated. Therefore, it will be interesting to look at the user reviews of popular OSS projects to understand the quality dimensions that users take note of.…”
Section: Related Workmentioning
confidence: 99%